Postharvest technology and value addition of watermelons (Citrullus lanatus): an overview - Innocent, Kutyauripo; Matenda, Rumbidzai Trust (Journal of Postharvest Technology, 2024)
This review article covers postharvest handling of red fleshed watermelons (Citrullus lanatus) as well as possible watermelon value-added products. The rate of biochemical and microbial reactions that take place after harvesting must be minimised so as to enhance the quality of watermelon products. In most cases the rind and the seeds of the watermelon are not utilised despite the fact that they contain some nutrients. The seeds and rind are thrown away after consumption of the pulp though in some African communities the seeds are used to make oil and often as a meat substitute and the rind is given animals as a feed. On a commercial scale the rind can be exploited to produce watermelon jam and a flour that can be an additive in baking. The watermelon seed flour can be incorporated in the formulation of weaning food. The watermelon pulp is used in the production of yoghurt, watermelon juice, wine and powder. All the components of the watermelon can be utilised